EFEKTIVITAS HIDROTERAPI (RENDAM KAKI AIR HANGAT) UNTUK MENGURANGI NYERI KAKI PADA PENDERITA RHEUMATOID ARTHRITIS - Muhamad Edo Karefo; Agrina Agrina; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Hydrotherapy (Hydrotherapy) is a treatment method using water to treat or relieve painful conditions and uses a "low-tech". The purpose of this study was to determine whether Hydrotherapy (Warm Foot Soak) can reduce leg pain in patients with Rheumatoid Arthritis. This research is a quantitative research using a Quasy Experiment research design. The research sample was 30 respondents with purposive sampling technique which was divided into 2 groups, namely 15 experimental respondents who were given a foot soak in warm water and 15 respondents in the control group who were not given a foot soak in warm water. Both groups continued to take Rheumatoid Arthritis drugs. The measuring instrument used is an observation sheet and a Numeric Rating Scale with a measurement of the level of pain scale pre-test on the first day and post-test for 3 days in a row after doing hydrotherapy (warm foot soak). The analysis using Wilcoxon and Mann Whitney test. There was a significant difference in mean pre-test and post-test pain scale levels levels in experimental group with p value 0.001, where as in control group no difference was found with p value 0.689. There was a significant difference in pain scale reduction as proven by the result of the significance value was 0.000 (<0,05). There is an effect of hydrotherapy on the pain scale level of Rheumatoid Arthritis. The results of this study are expected to be an alternative treatment in controlling pain scale level in patients with Rheumatoid Arthritis. Keywords : Effectiveness, Hydrotheraphy, Pain, Soaking Feet In Warm Water, Rheumatoid Arthritis